Model Arsitektur Pohon Di Kawasan Hutan Taman Wisata Alam, Desa Iboih, Kota Sabang, Pulau Weh - Muslich Hidayat; Kartika Wulandari; Arif Sardi (Yayasan Tajuk Indonesia, 2025)
Forests are vital ecosystem components that provide water, oxygen, habitat, and maintain environmental balance. Forest vegetation with a developed canopy reduces sunlight intensity reaching the ground, influencing microclimate. This study aims to identify the types and dominant models of tree architecture in the Gampong Iboih Nature Park (TWA) area, Weh Island, Sabang City. The method used was line transect at 8 stations with different elevations (5-200 masl). The results found 14 branch architecture models from 71 tree species, namely Koriba, Leeuwenberg, Schoute, Rauh, Prevost, Massart, Holttum, Tomlinson, Stone, Corner, Petit, Chamberlain, Attims, and Scarrone. The Koriba model was the most dominant with a percentage of 36.6%. This dominance indicates the forest's structural characteristics that influence its ecological functions, such as soil and water conservation